Distribution of Protein Precipitation Capacity within Variable Proanthocyanidin Fingerprints - Leppä Milla Marleena; Laitila Juuso Erik; Salminen Juha-Pekka (MDPI, 2022)
Proanthocyanidins (PAs) are highly bioactive plant specialized metabolites. One of their most characteristic features is their ability to precipitate proteins. In this study, eleven plant species were used to study the structure-activity patterns between PAs and their protein precipitation capacity (PPC) with bovine serum albumin. To obtain a comprehensive selection of PAs with highly variable procyanidin to prodelphinidin ratios and mean degree of polymerizations, nearly 350 subfractions were produced from the eleven plant species by semi-preparative liquid chromatography. Their PA composition was defined by tandem mass spectrometry and high-resolution mass spectrometry, and their PPC was measured with a turbidimetry-based well-plate reader assay. The distribution of the PPC within plant species varied significantly. The mean degree of polymerization of the PAs had a strong correlation with the PPC (r = 0.79). The other structural features were significant from the PPC point of view as well, but they contributed to the PPC in different ways in different plant species. Retention time, prodelphinidin proportion, and mean degree of polymerization explained 64% of the measured variance of the PPC.